Sensemaking and Big Data Science Used in Marketing to Solve Social and Behavioral Problems - Latta, Michael (Journal of Strategic Innovation and Sustainability, 2020)
The way Big Data Science was enabled through the marriage of technology in the form of computer science and the discipline of statistics was told by Gil Press in his (2013) Forbes piece titled ‘A Very Short History of Data Science.’ Data Science is now the discipline charged with utilizing Big Data. But making sense of data has a much longer history. Karl Weick (1993) introduced the concept of Sensemaking in organizational decision making to account for failures in data-driven decision making. This paper explores Sensemaking and Big Data Science being used in marketing to solve social and behavioral problems.